2021
DOI: 10.1021/acs.jpcc.1c06285
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties of the Hexagonal Ferromagnet NdCrGe3 Showing Metamagnetic Transition and Negative Magnetocaloric Effect

Abstract: Single crystals of a hexagonal ferromagnet NdCrGe 3 with one-dimensional crystal structure are synthesized, and the magnetic properties are comprehensively investigated, exhibiting large magnetic anisotropy and complex magnetic structure. Besides the ferromagnetic transition at T C = 101 K, we observe a sharp decrease in magnetization at T = 55 K and another two phase transitions at T = 31 and 15 K. These phase transitions imply complex and anisotropic magnetic structure in NdCrGe 3 . Below T = 55 K, metamagne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 105 publications
1
4
0
Order By: Relevance
“…5c), suggests a more complex ordering scheme. Similar behaviour was observed in some ternary R–T–E ferromagnets, such as NdMn 6 Sn 6 , NdMn 6 Ge 6 and NdCrGe 3 , 34–36 where magnetic moments do not align with the direction of the magnetic field upon ordering, but reorient themselves towards it upon further cooling. We propose that a similar process occurs for the Sm moments in our case as well.…”
Section: Resultssupporting
confidence: 78%
“…5c), suggests a more complex ordering scheme. Similar behaviour was observed in some ternary R–T–E ferromagnets, such as NdMn 6 Sn 6 , NdMn 6 Ge 6 and NdCrGe 3 , 34–36 where magnetic moments do not align with the direction of the magnetic field upon ordering, but reorient themselves towards it upon further cooling. We propose that a similar process occurs for the Sm moments in our case as well.…”
Section: Resultssupporting
confidence: 78%
“…In addition, a sharp decrease in magnetization below T = 55 K and negative MCEs are reported with applied field H//ab in single crystals of NdCrGe 3 . Moreover, two additional phase transitions at T = 31 and 15 K are reported in NdCrGe 3 , indicating complex low-temperature magnetic behavior [171]. Complex magnetic behavior in the RCrGe 3 family is reported, owing to the Nd-Cr magnetic interactions and strong magnetocrystalline anisotropy.…”
Section: Magnetic Propertiesmentioning
confidence: 81%
“…A c c e p t e d M a n u s c r i p t = 122 K and revealed both Cr and Nd moments are along the c axis of the hexagonal lattice [170]. Recently, a single crystals study of NdCrGe 3 reported a ferromagnetic transition at T C = 101 K; a lower transition temperature than than what was shown in the polycrystalline study [171]. In addition, a sharp decrease in magnetization below T = 55 K and negative magnetocaloric effects are reported with applied field H//ab in single crystals of NdCrGe 3 .…”
Section: Single Crystals Of Rvsbmentioning
confidence: 92%
“…Since the Arrott plots can not appropriately describe the magnetization in Co 7 Zn 8 Mn 5 , the modified Arrott plots (MAP) are utilized to characterize the M(H) curves. For systems with a second-order FM transition, the spontaneous magnetization (M s ) below T C , the M(H) curve at T C , and the initial magnetic susceptibility (χ −1 0 ) above T C are depicted by various critical exponents β, δ, and γ, respectively [47,48], To achieve proper critical exponents, an iterative way is utilized to determine the MAP [49][50][51][52], which successfully generates a series of parallel lines in the high-field region (figure 6(b)). Linearly extrapolated M s and χ −1 0 as a function of temperature are displayed in figure 7(a).…”
Section: Critical Behaviormentioning
confidence: 99%